Growing Teratoma Syndrome. (September 2015) - Merard, Reena; Ganesan, Raji; Hirschowitz, Lynn
<x xml:space="preserve">Abstract</x> We report 2 cases of growing teratoma syndrome (GTS) in patients who had been treated with surgery and chemotherapy for immature ovarian teratoma. One of the patients presented with probable paraneoplastic encephalitis. Resection of "recurrences" in both patients showed deposits of mature teratoma and extensive gliomatosis peritonei. It is important for both pathologists and clinicians to be aware of this uncommon entity to avoid misdiagnosis of GTS as recurrence of immature teratoma and disease progression, and to avert unnecessary continuation of chemotherapy. GTS may occur several years after diagnosis of the primary tumor, and rarely develop in treated patients who have become pregnant. Surgical debulking is the optimal modality of treatment as GTS is not chemosensitive. If surgical debulking of GTS is incomplete, long-term follow-up with imaging is required to avoid complications such as bowel obstruction and the sequelae of pressure effects (such as vascular thrombosis, fistula formation, etc.) from bulky deposits of mature teratoma/GTS and gliomatosis peritonei.